Some considerations about the use of lime-cement mortars for building conservation purposes in Portugal : a reprehensible option or a lesser evil? - Pacheco-Torgal, F. (2012)
Some investigations about conservation actions in historical buildings points out that lime–cement mortars should be avoided and lime–pozzolan mortars should be use instead. Nevertheless this type of mortar is still under investigation and the absolute rejection of the use of Portland cement even with just a minimum amount appears to be a dogmatic position that is not fully grounded in scientific terms. Besides the use of lime–pozzolan mortars requires skilled craftsmanship and at least in the case of the majority of Portuguese construction enterprises operating in the field of building conservation these conditions are not assured. These facts can influence the decision about the mortars choice for conservation purposes, since in certain circumstances it may be preferable to apply lime–cement mortars instead of an incorrect application of lime–pozzolan mortars.